PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN HIDROKARBON DI KELAS X SMA NEGERI 1 TAMBANG (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aimed to increase students achievement by implementation of learning cooperative type Group Investigation on learning topic of Hydrocabon in class X SMA N 1 Tambang. The type of this research is experimental research with randomized control group pretest-posttest design. Subject of this research are X 1 as the experimental class, X 2 as the control class which were determined randomly after conducting normality and homogeneity test. The experimental group was treated with the implementation of learning cooperative type group investigation while the control group without the implementation of learning cooperative type group investigation. The data analysis to test the hypothesis was used t-test right side. Based on the data analysis, it is obtaine tcount = 2,09 and ttable = 1,67 with α=0,05, dk = 54, tcount > ttable is 2,09 > 1,67, It’s mean that the implementation of learning cooperative type group investigation can improve students achievement on the subject of colloid in XI IPA SMA Negeri 12 Pekanbaru. Category of improvement of students achievement in the experimental class of 11,2%.Keywords: Learning cooperative type group investigation, learning achievement